2021
DOI: 10.1177/1358863x211055507
|View full text |Cite
|
Sign up to set email alerts
|

Images in Vascular Medicine: Leukocytoclastic vasculitis after COVID-19 vaccine booster

Abstract: A 65-year-old man developed purpuric palpable lesions of the legs 2 days after receiving his third dose (booster) of Pfizer BioNTech vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Panels A and B). He received his initial vaccinations 4 months prior to receiving his booster injection. He denied any prior SARS-CoV-2 infection. He denied any systemic symptoms. The patient has a history of diabetes and hypertension for which he is on metformin and lisinopril, respectively; he oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty cases of COVID‐19‐vaccine triggered‐LCV were noted; three with an elevated anti‐Spike SARS CoV‐2 Antibody titer, two of them had no history of COVID‐19.Oral mucosal involvement was noted in one case. Only one had cryoglobulinemia 7,18–33,36,37 . Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Among the available COVID‐19 vaccines, LCV has been reported with messenger RNA‐based vaccines (BNT162b2 [Pfizer‐BioNTech] 6,8–12 and mRNA‐1273 [Moderna], 6,7 adenoviral vector‐based vaccines [ChAdOx1 nCoV‐19; Oxford‐AstraZeneca]), 13–19 and inactivated vaccines (Covaxin, 20,21 Sinovac, 22,23 and unspecified inactivated vaccines 24 ) (Table 1). Most of the reported vaccine‐related cutaneous LCV were limited to the skin and only few were associated with systemic involvement 7,9,11,19,23 .…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Another potential cause for the occurrence of vasculitis is the use of thiazides, which has been known for many years (1) .Although our patient received a low dose of hydrochlorthiazide (HCTZ) (25mg once daily ), drug induced vasculitis due to HCTZ could not be ruled out . Finally, we were curious whether the administration of COVID vaccines could result in vasculitis .Although there have recently been some reports about the use of mRNA based COVID vaccines as a cause of leukocytoclastic vasculitis (8)(9)(10)(11)(12) , the role of inactivated whole virus vaccines such as Sinopharm , Sinovac (CoronaVac) and COVAXIN (Bharat Biotech) should not be overlooked (13)(14)(15) .…”
Section: Discussionmentioning
confidence: 99%